A Review of Tropical Organic Materials for Biodiesel as a Substitute Energy Source in Internal Combustion Engines: A Viable Solution? - Anderson Breno Souza; Alvaro Antonio Villa Ochoa; José Ângelo Peixoto da Costa; Gustavo de Novaes Pires Leite; Héber Claudius Nunes Silva; Andrezza Carolina Carneiro Tómas; David Campos Barbosa; Paula Suemy Arruda Michima (Energies, 2023)
In this article, the most important publications on the subject are compiled to highlight the progress in biodiesel production from tropical cultivars, including energy and environmental potential, raw materials, and the advantages and disadvantages of this biofuel. A critical and objective review of biodiesel production as an alternative fuel for power generation systems and its importance in the energy matrix was conducted. A survey of real applications, new computational and experimental trends, and proposals in internal combustion engines employing organic biofuel was performed. The main findings were as follows: (i) there is the possibility of integration and support in the energy matrix of different countries, as well as the competing with and complementing, energetically, other renewable energy sources, such as solar and wind; (ii) Jatropha curcas, sunflowers, soybean, Moringa oleifera, palm, cottonseed, castor, rubber seed, and coconut are tropical cultivars used to obtained oils into biodiesel; (iii) the findings can be utilized as a theoretical basis for future policies influencing the energy sector through regulatory measures.